Eliciting Spill - Alvita Nathaniel (Grounded Theory Review: An International Journal, 2008)
Classic grounded theory is an inductive process that focuses on the experiences and perceptions of research participants (Glaser, 1978, 1998). Although grounded theorists may utilize other types of data, most are likely to gather information through qualitative interviews. The theorist seeks to understand what is going on as people resolve their main concern in a given substantive area. People know what is important to them and most want to tell their stories. They feel encouraged to talk when they recognize that their stories are valued. Once the informant realizes that he or she is being heard, the story flows. This is what Glaser refers to as “spill.” When this occurs, the theorist becomes a vessel to receive the story. As Glaser describes it, “The researcher will become a ‘big ear’ to pour into incessantly” (1998, p. 124). But, as easy as this seems, the researcher must overcome certain positivist tendencies to allow this to happen. Rather than asking a list of pre-planned questions, the grounded theorist will try to develop one question that will trigger the telling of a story. Eliciting spill requires a deliberate process that employs a deep understanding of the fundamentals of classic grounded theory. Derived from Glaser’s writings, the following are suggestions intended to help the novice grounded theorist to elicit spill.